Combining microscale ATR-FTIR and chemometrics to interpret degradation characteristics of earlywood, latewood, and compression wood in waterlogged archaeological pine wood - Ren Li; Zhiguo Zhang; Lichao Jiao; Yafang Yin; Fude Tie; Manli Sun (Heritage Science)
Abstract Interpreting the degradation characteristics of waterlogged archaeological wood (WAW) is crucial for the conservation of wooden cultural heritage. Generally, multidisciplinary diagnostic methods, including physical, micromorphological, and chemical approaches, are employed to evaluate the preservation state of WAW. However, primarily focused on the sample level, this methodology limits the understanding of the variability in degradation from a detailed perspective. In this paper, we adopted the in-situ microscale attenuated total reflectance Fourier transform infrared (ATR-FTIR) method to investigate the degradation variability in waterlogged archaeological Masson pine (Pinus massoniana) wood excavated from the ancient Chinese shipwreck Nanhai No. 1. Specifically, spectra of earlywood (EW), latewood (LW), and compression wood (CW) were extracted and combined with chemometrics to achieve rapid classification of their degradation levels. The micromorphological features of wood cell walls in conjunction with the ratios of lignin (A1509) and carbohydrate (A1370) peak areas were used to estimate the degradation levels. Unlike recent wood, moderate degradation in CW and severe degradation in EW and LW were classified in archaeological samples. The degradation levels were effectively determined through principal component analysis (PCA) and sparse partial least squares discriminant analysis (sPLSDA). The results suggest that chemometric analysis is a promising method to discern the variable degradation levels of archaeological wood at the tissue level. The methodologies developed in this study provide detailed insights into the degradation characteristics in WAW and improve the accuracy of evaluating the preservation state.